Reduction of stress and blood pressure with meditation therapy in elderly groups in balai pelayanan sosial tresna werdha (BPSTW) in Yogyakarta - Fajarina Lathu A (International Journal of Health Science and Technology, 2019)
Stress in elderly institution residents is an interesting phenomenon to study. Sustained stress in the elderly can be harmful and cause mental and physical health problems. Hypertension is one of the physical health problems that can result from stress. Nursing Intervention Classification 2013 recommends the use of Meditation Therapy to address the problem. Meditation is a self-directed exercise to relax and calm the mind, besides that meditation is an easy and inexpensive activity. This certainly provides benefits for the institution in caring for the elderly. Less information on meditation therapy, challenging nurses to perform scientific verification.Scientific proof of reduced stress and blood pressure in elderly groups at the Balap Pelayanan Tresna Werdha (BPSTW) in Yogyakarta This research is a quasy experiment with pretest and posttest with control group. The treatment group was given meditation therapy for 7 times a week, while the control group was not given treatment. Respondents were selected using simple random sampling. Stress measurement using the DASS (Depression Anxiety Stress Scale) and blood pressure were measured using a digital sphygmomanometer. The stress in intervention group of elderly after being treated results decreased by 1.8, whereas in the control group it increased by 0.029. The systole blood pressure in the intervention group of elderly decreased 6.257 mmHg and 0.457 mmHg in the control group. When the elderly diastole blood pressure in the intervention group experienced an average decrease of 3.4 mmHg, while in the control group it increased by 1.057 mmHg. Conclusion: Meditation therapy is significant for reducing stress and blood pressure in the elderly at the Balai Pelayanan Tresna Werdha (BPSTW) in Yogyakarta